‘The Word Became Image’: The Use of Magic Lanterns in Mission and Evangelism by British Baptists - Smith, Karen E. (Baptist quarterly, 2022)
Drawing on the study by T. Jack Thompson, Light On Darkness? Missionary Photography of Africa in the Nineteenth and Early Twentieth Centuries (Grand Rapids: Eerdmanns, 2012), this paper explores, more specifically, the use of the Magic Lantern by British Baptists at home, and in missionary activity around the world, in the late Nineteenth and early Twentieth centuries. Given the widespread use of Magic lantern presentations among children and adults in Baptist life, and taking into account the vast collection of slides in the Angus Library, this article highlights the need for further study of the way images have shaped Baptist approaches to mission, as well as worship and devotion.